Innovation Systems and Developing Countries: Experiences from the SUDESCA Project. - Segura-Bonilla, Olman (2001)
This report deals with the transfer of knowledge from the North to the South. More specifically it deals with a Danish development aid project which aims at enhancement of research capacity in some Central American countries. First, some difficulties connected to knowledge transfer between North and South are discussed on a general level. It is argued that these difficulties are connected to contradictions in the globalising learning economy: On the one hand short-term economic calculations and speedy processes of decision-making are getting more and more important. On the other hand competition depends more and more on dynamic efficiency rooted in knowledge or knowledge related resources with long term characteristics. After this some concrete experiences from a specific project aiming at building research capacity about sustainable development strategies - the SUDESCA project – are presented. This project is carried out within a system of innovation approach and it is argued that this concept needs to be adapted in order to be useful in the context of developing countries. It is concluded that the results of projects like this depends on to which extent processes of intercultural learning can be organised and if they can be sustained for longer periods of time